2019
DOI: 10.1186/s13620-019-0142-8
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin treatment failure on four Irish dairy farms

Abstract: We report on the use of the faecal egg count reduction test to evaluate the performance of ivermectin in treating gastrointestinal nematode infections in first grazing season (FGS) calves on four dairy farms in Co. Kilkenny, Ireland. On each farm, FGS calves were injected subcutaneously with ivermectin in accordance with their live weight (day 0). Calves were individually faecal sampled on both day 0 and day 14. Faecal egg counts were determined using the Mini-FLOTAC technique. Composite faecal cultures for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Therefore, these farms may not be truly representative of all dairy calf to beef farmers in Ireland. Notwithstanding this, other studies have confirmed that IVM resistance is common on cattle farms in Ireland, albeit few farms have been previously tested [19,20]. Prior to this study, testing for AR had only occurred on one farm although some farmers reported that they perceived IVM had become less effective.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, these farms may not be truly representative of all dairy calf to beef farmers in Ireland. Notwithstanding this, other studies have confirmed that IVM resistance is common on cattle farms in Ireland, albeit few farms have been previously tested [19,20]. Prior to this study, testing for AR had only occurred on one farm although some farmers reported that they perceived IVM had become less effective.…”
Section: Discussionmentioning
confidence: 85%
“…There are over 92,000 farms in Ireland, of which over 54,000 are classed as cattle rearing and fattening enterprises, which includes both dairy calf to beef and suckler beef production [26]. Despite the importance of this sector to the agricultural industry in Ireland, and the industry's reliance on a grass-based production system, there is a distinct lack of information on the prevalence of AR among GIN of cattle in Ireland, although resistance to IVM has been reported [19,20]. This study provides clear evidence for resistance to all commonly available anthelmintic classes among GIN of cattle in Ireland, including resistance to IVM in Ostertagia spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…egg is found [ 11 , 22 , 57 ]. In contrast, for a faecal egg count reduction test (FECRT) to identify drug-resistant nematode populations, a sensitive and precise quantitative method is required, and the Mini-FLOTAC method has been repeatedly shown to perform very well in FECRT studies [ 63 65 ], including studies on horses [ 32 , 66 68 ]. Reasons to consider when choosing a test based on convenience include access to the laboratories that offer tests and acceptable turnaround times for results.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of widespread antimicrobial resistance (AMR) exhibited now by many commonly encountered pathogens including bacteria (e.g., Gram-positive: Staphylococcus aureus , Streptococcus pyogenes , Mycobacterium tuberculosis , and Clostridium difficile ; and Gram-negative: Escherichia coli , Klebsiella pneumoniae , Salmonella typhi , Pseudomonas aeruginosa , and Neisseria gonorroheae ), viruses (e.g., hepatitis B and C, herpes, and influenza), and fungi (e.g., Candida albicans , Aspergillus fumigatus , and Cryptococcus neoformans ) against a range of popular antimicrobials, such as β-lactam antibiotics, macrolides, tetracyclines, aminoglycosides, fluoroquinolones, antihelminthics, and antifungals ( Singer et al., 2016 ; Naylor et al., 2018 ; Hofer, 2019 ; Laws et al., 2019 ), in both human and veterinary medicine, such as the resistance noted against ivermectin in animal husbandry ( O’Shaughnessy et al., 2019 ), is a major challenge today. Indiscriminate use of antibiotics due to their widespread availability and over-the-counter sales, often without prescription and in conjunction with poor sanitation, inadequate water purification, and wastewater management, as often occurs in developing countries, is posited to be a prime contributing factor to the surge of multidrug-resistant (MDR) strains, including methicillin-resistant Staphylococcus aureus (MRSA, Okwu et al., 2019 ) and vancomycin-resistant Enterococcus (VRE; Cetinkaya et al., 2000 )—collectively termed as the superbugs ( Davies and Davies, 2010 ; Khan and Khan, 2016 ).…”
Section: Introductionmentioning
confidence: 99%